Mao. 21 - Takahashi, Rumiko, 1957-; Roman, Annette (Shōnen Sandē komikkusu., 2025)
"Mao attempts to save the victim of a curse as well as the one who cast it. Then, a case of missing children attracts the attention of both our friends and the Goko clan. Next, a puppeteer creates dangerous, living dolls. Sometimes it's hard to tell the perpetrator from the victim...and sometimes they're one and the same."--Publisher's website.